‘Expulsion’ in German historical policy — consequences for Polish-German relations - Bojenko-Izdebska, Ewa (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
After the Second World War constant controversies and confrontations between Poland and Germany were provoked, in addition to question of the recognition of Poland’s western border, by the “fl ight and expulsion” Flucht und Vertreibung of Germans — described as “population transfer” by the Polish side — and the activity of homeland associations. In the early 1990s, after the fi nal recognition of the border and in view of the growing collaboration in many fi elds, it could seem that the controversies were resolved. However, the problem of “expulsions” returned in the 21st century with a new German historical policy and institutionalisation of remembrance. The change was symbolised by the Centre Against Expulsions project of 2002. In the end the German Bundestag adopted a resolution establishing a documentation centre of the Foundation Flight, Expulsion, Reconciliation in Berlin. In 2017 the centre presented a concept for a permanent exhibition. Its opening is planned for 2019. The controversies surrounding both projects have had an impact on the Polish-German relations and have revealed the diff erences in historical policies of the two countries.
Keywords: wydalenia; uchodźcy; przymusowa migracja; przemieszczenie; pojednanie; niemiecka polityka historyczna; pamięć narodowa; stosunki polsko-niemieckie